The Trump indictments : the historic charging documents with commentary - Murray, Melissa; Weissmann, Andrew (W. W. Norton & Company, 2024)
"Timed to the start of the first trial in March 2024, this essential volume collects the four unprecedented indictments against Donald Trump and features extensive commentary by NYU law professors and MSNBC contributors Melissa Murray and Andrew Weissmann. In the long span of American history, Donald Trump is the first former president to face criminal indictment. He is the subject of a series of explosive charges across four cases: the January 6 case brought by Special Counsel Jack Smith; the election interference case in Georgia; the classified documents case also brought by Special Counsel Jack Smith; and the "hush money" case in New York"--